Proceedings of the international symposium on water quality modeling of agricultural non-point sources, Utah State Univrsity, Logan, Utah, June 19 - 23, 1988 - International Symposium on Water Quality Modelling of Agricultural Non-Point Sources (1988 : Logan, Utah); DeCoursey, Donn G. (United States Department of Agriculture, 1990)
07